2017
DOI: 10.1097/qai.0000000000001394
|View full text |Cite
|
Sign up to set email alerts
|

Association of CD4+ T-cell Count, HIV-1 RNA Viral Load, and Antiretroviral Therapy With Kaposi Sarcoma Risk Among HIV-infected Persons in the United States and Canada

Abstract: Background Kaposi sarcoma (KS) remains common among HIV-infected persons. To better understand KS etiology and to help target prevention efforts, we comprehensively examined a variety of CD4+ T-cell count and HIV-1 RNA viral load (VL) measures, as well as antiretroviral therapy (ART) use, to determine independent predictors of KS risk. Setting North American AIDS Cohort Collaboration on Research and Design. Methods We followed HIV-infected persons during 1996-2009 from 18 cohorts. We used time-updated Cox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 58 publications
9
37
0
3
Order By: Relevance
“…Ritonavir‐based, indinavir†‐based or nelfinavir*‐based therapy confers no advantages compared to other PI‐ or NNRTI‐based regimens in the prevention of ADCs . This is in line with the fact that the HAART impact on the decrease of ADCs is mainly connected with improvement in immune function and viral load . At the same time, some studies showed potential advantages of PI‐based HAART in ADCs prevention over other regimens.…”
Section: Comparison Between Haart Regimens In Terms Of Cancer Preventionmentioning
confidence: 86%
See 4 more Smart Citations
“…Ritonavir‐based, indinavir†‐based or nelfinavir*‐based therapy confers no advantages compared to other PI‐ or NNRTI‐based regimens in the prevention of ADCs . This is in line with the fact that the HAART impact on the decrease of ADCs is mainly connected with improvement in immune function and viral load . At the same time, some studies showed potential advantages of PI‐based HAART in ADCs prevention over other regimens.…”
Section: Comparison Between Haart Regimens In Terms Of Cancer Preventionmentioning
confidence: 86%
“…The protective effect of HAART is mainly explained by virus inhibition and immune restoration. Although at first it was thought that HAART had an additional protective effect independent of CD4 cell count and viral load, the latter studies did not detect any independent effect of HAART on Kaposi sarcoma incidence after adjusting for more variables and in a larger cohort …”
Section: Hiv and Cancer Treatment In The Haart Eramentioning
confidence: 91%
See 3 more Smart Citations